(untitled) (Journal of Management and Social Sciences, 2016)
For any nation to experience growth and accelerated development, conscious efforts have to be made in terms of socio-economic inclusion of the entire citizenry, good governance and ensuring justice in all spheres. This paper advocates some Islamic elements of governance and economic blueprint as panacea for development that will culminate to a harmonious communal living devoid of sectional schisms and economic exploitation of the majority by the few. The Islamic institutions of Zakaat (Compulsory Annual Charity), Sadaqah (Voluntary Alms), Kaffaarah (Atonement Feeding) and Zakaatul-Fitr (End-of-Ramadhan Charity) that are effective instruments of redistribution of wealth and bridging the gap between the affluent and the destitute were proposed for adoption by Sub-Saharan Africa in order to achieve the much sought national reconciliation, economic prosperity and survival justice for all. The paper concludes that it is only through good governance and economic emancipation of people that genuine progress and real nationhood can be achieved. Keywords Good governance, Sadaqah, economic prosperity, Zakaat, Zakaatul-Fitr, empowerment